(untitled) (BIRDEM Medical Journal, 2020)
Background: Stunting is a major public health problem in Africa, where more than one-third of below 5 years children are stunted. The aim of this paper is to find relation of daily dietary intake of <5 years old children with their height for age status in Burundi. Method: A literature review was done using CINAHL, PubMed, Medline. A grey literature search was done using Google scholar and Bing. The most recent Demographic and Health Survey (DHS) data from the target country was used for the data analysis. The analysis contains the data pertaining to children <5 years of age. Results: information of a total of 6096 children were included in the study among them 55% of children were stunted. Female children are more susceptible to stunting than the male. Children living in rural areas have a higher possibility of having below normal height for age. Children who did not consume milk and sugar in the previous day (1.809 times higher risk and 1.542 times higher risk respectively) are at higher risk of being stunted relative to the normal child. Children who are born in a twin (AOR OR = 3.4, 95% CI = 1.875-6.104) or triplet (AOR = 6.9, 95% CI = 3.204-14.736) pregnancy have high risk of being stunted. The relative risk of stunting increases in people who are in a low socio-economic class. Conclusion: Findings from this national-level data clearly show that there is a need for interventions addressing macro-nutrient deficiency along with special attention to micro-nutrients supplements can solve the problem of stunting in Burundi. Birdem Med J 2020; 10(2): 108-114